PELAKSANAAN PEMBAGIAN WARIS ISLAM DI KESULTANAN KUTAI KARTANEGARA ING MARTADIPURA - , Bruri Yahma Pribadi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research, titled âIslamic Division of Inheritance at the Kutai Kartanegara Ing Martadipura Sultanate,â aims to determine the application of Islamic division of inheritance at the Sultanate of Kutai Kartanegara Ing Martadipura and the factors that influence its operation. This research is an empirical juridical research â that is, a research which emphasizes on collecting field information to obtain the primary data. The secondary data is obtained through bibliographic studies by tracing primary, secondary, as well as tertiary legal materials. The whole obtained data were analysed qualitatively. Based on the research results, conclusions were drawn, which also serve to answer questions raised by the author. That the application of Islamic division of inheritance at Kutai Kartanegara Ing Martadipura Sultanate emphasizes solution through dialog and deliberation in applying the division. That the factors which influence the aplication of Islamic division of inheritance at Kutai Kartanegara Ing Martadipura Sultanate include societyâs level of knowledge on the Islamic Laws of Inheritance, government regulations, local custom, and education.